Mild and Arid Climate in the Eastern Sahara‐Arabian Desert During the Late Little Ice Age. Issue 14 (20th July 2018) - Felis, Thomas; Ionita, Monica; Rimbu, Norel; Lohmann, Gerrit; Kölling, Martin
Abstract: The climate of the Sahara and Arabian Deserts during the Little Ice Age is not well known, due to a lack of annually resolved natural and documentary archives. We present an annual reconstruction of temperature and aridity derived from Sr/Ca and oxygen isotopes in a coral of the desert‐surrounded northern Red Sea. Our data indicate that the eastern Sahara and Arabian Deserts did not experience pronounced cooling during the late Little Ice Age ( 1750–1850) but suggest an even more arid mean climate than in the following 150 years. The mild temperatures are broadly in line with predominantly negative phases of the North Atlantic Oscillation during the Little Ice Age. The more arid climate is best explained by meridional advection of dry continental air from Eurasia. We find evidence for an abrupt termination of the more arid climate after 1850, coincident with a reorganization of the atmospheric circulation over Europe. Plain Language Summary: The Little Ice Age ( 1450–1850) is thought to have been characterized by generally cold conditions in many regions of the globe with little similarities regarding the hydroclimate. The climate of the Sahara and Arabian Deserts during the Little Ice Age is not well known, due to a lack of annually resolved sedimentary, tree ring, speleothem, and documentary archives in these uninhabited arid regions. We present an annual reconstruction of temperature and aridity derived from Sr/Ca and oxygen isotopes in a coral of northern Red Sea, a narrow ocean basin bounded by the eastern Sahara and Arabian Deserts. Our data indicate that these desert areas did not experience pronounced cooling during the late Little Ice Age ( 1750–1850) but suggest an even more arid mean climate than today. The mild temperatures and more arid climate are attributed to a changed atmospheric circulation at that time. We find an abrupt termination of the more arid climate after 1850, coincident with a reorganization of the atmospheric circulation over Europe at the end of the Little Ice Age. Our study highlights the need for temperature and aridity reconstructions from the global deserts to detect the full range of climate change over the Common Era. Key Points: Coral Sr/Ca and oxygen isotope records of the northern Red Sea provide annual reconstructions of temperature and aridity back to 1750 The eastern Sahara‐Arabian Desert region did not experience pronounced cooling during the late Little Ice Age ( 1750‐1850) The late Little Ice Age climate of the eastern Sahara‐Arabian Desert was even more arid than today and ended abruptly around 1850